Digest: Fossils, evolutionary models, and diatoms. (3rd December 2019) - Khodaei, Lucas
Abstract: Adaptation to new environments by organisms has been and is of much interest in scientific research. Does the diatom lineage Stephanodiscus niagarae / yellowstonensis follow models compatible with adaptation to a new environment? Voje (2019) shows that in this lineage, none of the current models tested—decelerated evolution, Ornstein‐Uhlenbeck, and random walk—fully explained how multiple traits—valve diameter, the number of costae, and spines per valve—evolved. More accurate models are needed to understand the evolutionary history of these diatoms.